Smart technologies - Mireille Hildebrandt (Internet Policy Review)
Speaking of ‘smart’ technologies we may avoid the mysticism of terms like ‘artificial intelligence’ (AI). To situate ‘smartness’ I nevertheless explore the origins of smart technologies in the research domains of AI and cybernetics. Based in postphenomenological philosophy of technology and embodied cognition rather than media studies and science and technology studies (STS), the article entails a relational and ecological understanding of the constitutive relationship between humans and technologies, requiring us to take seriously their affordances as well as the research domain of computer science. To this end I distinguish three levels of smartness, depending on the extent to which they can respond to their environment without human intervention: logic-based, grounded in machine learning or in multi-agent systems. I discuss these levels of smartness in terms of machine agency to distinguish the nature of their behaviour from both human agency and from technologies considered dumb. Finally, I discuss the political economy of smart technologies in light of the manipulation they enable when those targeted cannot foresee how they are being profiled.